“Sorting hat” flap as a modification of the classic A-T flap - Giulio Gualdi; Alessandra Petruzzellis; Cesare Ariasi; Paolo Amerio; Paola Monari (Dermatology Reports, 2024)
This article presents a case study featuring a novel modification of the A-T flap, termed the "Sorting Hat" flap, employed in dermatologic surgery for facial reconstruction. In the treatment of an 89-year-old male's squamous cell carcinoma lesion on the forehead, the "Sorting Hat" flap, introduced as an innovative alternative, eliminates the need for Burrow triangles and relies on flap shape for inconspicuous scarring and favorable cosmetic outcomes.